TAX LAW ENFORCEMENT IN THE PANDEMIC TIME COVID 19 - Bambang Ali Kusumo (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Legal sanctions in the field of taxation consist of administrative sanctions and criminal sanctions, but in their implementation administrative sanctions are prioritized, considering that administrative sanctions are more profitable, because the time required is not too long and money can immediately enter the state treasury, but the weakness is that there is a lack of a good deterrent effect. against the perpetrator and potential perpetrator. In law enforcement, legal sanctions may not be enforced or their enforcement is postponed due to unavoidable disasters such as during the Covid 19 pandemic. Keyword: law enforcement, administrative sanctions, criminal sanctions.